STAKEHOLDER PERSPECTIVES ON WORLD HERITAGE AND DEVELOPMENT IN AFRICA - Taruvinga, Pascall ([S.l.] : ROUTLEDGE, 2022)
Stakeholder Perspectives on World Heritage and Development in Africa argues that World Heritage Sites (WHS)across the African continent should adopt practical, innovative, creative, andalternative management approaches that bring greater socio-economic benefits to society, whilst protecting their Outstanding Universal Value. Drawing on empirical evidence gathered in conversation with stakeholders at WHS across Africa, the book explores the challenges involved in implementing conservation and socio-economic development as a stakeholder-driven process. Demonstrating that heritage can no longer be viewed as totally separate from its socio-economic context, Pascall argues that decisions about the management of heritage need to make sense at the local level if they are to be supported by stakeholders. As the book shows, heritage is still viewed and managed through systems, approaches, and strategies inherited from the colonial period, despite the increasing availability of inclusive governance systems. Stakeholders offer alternative, creative, and innovative approaches that capitalize on the potential of World Heritage to contribute to socio-economic development, whilst ensuring that its credibility and integrity are maintained. Stakeholder Perspectives on World Heritage and Development in Africa offers unique insights into local perspectives on World Heritage and development in Africa. The book will be essential reading for academics, students, development partners, and practitioners around the world who are interested in museums and heritage, conservation, development, and the African continent. Also, the book will be useful in the preparation of nomination dossiers, management plans, development plans, and in disaster risk management at WHS.
OCLC-licensed vendor bibliographic record.
Keywords: Cultural property -- Africa; Historic sites -- Africa; Natural areas -- Africa; Economic development -- Africa; World Heritage areas -- Africa; Stakeholder management -- Africa; BUSINESS & ECONOMICS / Development / Economic Development; HISTORY / Africa / General